Full state control of a Fury X-Cell unmanned helicopter - Van Schalkwyk, Carlo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.